A Comparative Study on Conventional Network and Software Defined Network - Khavya, K.; Vairam, T. (Indian Journal of Computer Science, 2019)
Software Defined Networking (SDN) is the next big technology in networking. It decouples the network control plane from the forwarding plane and it has the central controller that is programmatic. The entire network is controlled by the central controller. SDN is automated, reliable, cost-efficient, agile, and dynamic in nature. This paper reviews the study on traditional network and SDN. The comparison is based on the different protocols used, firewalls, control plane, and few other basic parameters such as reliability, vulnerability, error control, architecture, and cost parameters. As a result of comparison, it is evident that SDN is more efficient than the traditional network architecture.